PI3-Kinase δγ Catalytic Isoforms Regulate the Th-17 Response in Tuberculosis - Leisching, Gina R. (Frontiers in Immunology, 2019)
Although IL17A plays a protective role at the mucosal surface, when IL17A signaling becomes dysregulated, a pathological response is locally induced. At the early stages of Mycobacterium tuberculosis (M.tb) infection, IL17A contributes to granuloma formation and pathogen containment. In contrast, during disease progression, a dysregulated IL17A hyperinflammatory response drives tissue destruction through enhanced neutrophil recruitment. Cumulative research has implicated the PI3-Kinase pathways as one of the most relevant in the pathophysiology of inflammation. Evidence shows that IL-17A secretion and the expansion of the Th17 population is dependant in PI3-Kinase signaling, with the p110δ and p110γ isoforms playing a prominent role. The p110γ isoform promotes disease progression through dampening of the Th17 response, preventing pathogen clearance and containment. The p110γ gene, PIK3CG is downregulated in TB patients during late-stage disease when compared to healthy controls, demonstrating an important modulatory role for this isoform during TB. Conversely, the p110δ isoform induces IL-17A release from pulmonary γδ T-cells, committed Th17 cells and promotes neutrophil recruitment to the lung. Inhibiting this isoform not only suppresses IL-17A secretion from Th17 cells, but it also inhibits cytokine production from multiple T-helper cell types. Since increased IL-17A levels are observed to be localized in the lung compartments (BAL and lymphocytes) in comparison to circulating levels, an inhalable PI3Kδ inhibitor, which is currently utilized for inflammatory airway diseases characterized by IL-17A over-secretion, may be a therapeutic option for active TB disease.